Analysis of MicroRNAs in Biological Samples - Khan, Nasrin (Université d'Ottawa / University of Ottawa, 2015)
MicroRNAs (miRNAs) are a class of small, single-stranded, non-protein coding RNA molecules that regulate cellular messenger RNA (mRNA) and protein levels by binding to specific mRNAs. Aberrant miRNA expression has been shown to be implicated in several diseases, including cancer. Extracellular miRNAs have been found to circulate in the bloodstream and some of their levels have been associated with different diseases. Furthermore, they hold promise as tissue- and blood-based biomarkers for cancer classification and prognostication. Blood-based biomarkers are attractive for cancer screening due to their minimal invasiveness, relatively low cost and ease of reproducibility. New miRNA analysis techniques will add toward the understanding of their biological functions. In this thesis, I investigate the utility of capillary electrophoresis (CE) and mass spectrometry (MS) for analysis of miRNAs through proof-of-concept experiments. In the fi rst part of this work, we developed a Protein-Facilitated Affinity Capillary Electrophoresis (ProFACE) assay for rapid quantification of miRNA levels in blood serum (see List of publications (6)). We also implemented a capillary electrophoresis with laser induced fluorescence detection (CE-LIF) method with online sample pre-concentration for detection of endogenous microRNAs in human serum and cancer cells. 3' modification of miRNA is a physiological and common post-transcriptional event that shows selectivity for specific miRNAs and is observed across species. Recent studies have shown that post-transcriptional addition of nucleotides to the 3' end of miRNAs is a mechanism for miRNA activity regulation. For example, such modifications in plants and C. elegans influence miRNA stability. In humans, effects on miRNA stability and on mRNA target repression have both been observed. Thus, there is a need for miRNA detection techniques which are direct and multiplexed, require minimal sample preparation and provide qualitative information regarding these modifications. We developed a multiplexed miRNA detection technique based on capillary electrophoresis coupled on line with electrospray ionization mass spectrometry (CE-ESI-MS). This method allowed a label-free, direct detection of multiple miRNAs extracted from cancer serum as well as their post-transcriptional modifications with a high mass accuracy.
Keywords: MicroRNA; Capillary Electrophoresis; Laser induced fluorescence detection; Circulating miRNA; Post-transcriptional modification; Mass Spectrometry